Striatal Stimulation Nurtures Endogenous Neurogenesis and Angiogenesis in Chronic-Phase Ischemic Stroke Rats - Takamasa Morimoto; Takao Yasuhara M.D., Ph.D.; Masahiro Kameda; Tanefumi Baba; Satoshi Kuramoto; Akihiko Kondo; Kazuya Takahashi; Naoki Tajiri; Feifei Wang; Jing Meng; Yuan Wen Ji; Tomohito Kadota; et al. (Cell Transplantation, 2011)
Deep brain stimulation (DBS) is used to treat a variety of neurological disorders including Parkinson's disease. In this study, we explored the effects of striatal stimulation (SS) in a rat model of chronic-phase ischemic stroke. The stimulation electrode was implanted into the ischemic penumbra at 1 month after middle cerebral artery occlusion (MCAO) and thereafter continuously delivered SS over a period of 1 week. Rats were evaluated behaviorally coupled with neuroradiological assessment of the infarct volumes using magnetic resonance imaging (MRI) at pre- and post-SS. The rats with SS showed significant behavioral recovery in the spontaneous activity and limb placement test compared to those without SS. MRI visualized that SS also significantly reduced the infarct volumes compared to that at pre-SS or without SS. Immunohistochemical analyses revealed a robust neurogenic response in rats that received SS characterized by a stream of proliferating cells from the subventricular zone migrating to and subsequently differentiating into neurons in the ischemic penumbra, which exhibited a significant GDNF upregulation. In tandem with this SS-mediated neurogenesis, enhanced angiogenesis was also recognized as revealed by a significant increase in VEGF levels in the penumbra. These results provide evidence that SS affords neurorestoration at the chronic phase of stroke by stimulating endogenous neurogenesis and angiogenesis.